Source Model for the 2022 Qinghai Menyuan Ms 6.9 Earthquake Based on D-InSAR - Liao, Jiangtao; Liang, Chuntao; Wang, Chaoliang; Cao, Feihuang; Ye, Chengming; Yang, Yinghui (Frontiers in Earth Science, 2022)
On January 8, 2022, an Ms 6.9 earthquake occurred in Menyuan County, Qinghai Province, China. This earthquake ruptured a patch of the Qilian-Haiyuan fault in the northeast margin of the Qinghai-Tibet Plateau. In order to understand the seismogenic structure of this earthquake and analyze the fault activity, we use differential synthetic aperture radar interferometry (D-InSAR) technology to obtain a complete co-seismic displacement field on the surface, and use pixel tracking algorithm to extract the trace of the ruptured fault. The slip distribution of the seismogenic fault was inverted using the steepest descent method, and the Coulomb stress change caused by the earthquake was also calculated. Surface deformation results show that the Menyuan earthquake produced obvious surface displacements in an area of 50 x 40 km2. The displacements are mainly distributed in the western segment of the Lenglongling fault and the eastern segment of the Tolaishan fault. The maximum displacements in the ascending and descending orbits in the LOS direction are 59.7 cm and 94.7 cm, respectively. The co-seismic slip results show that the strike, dip and average slip angles of the seismogenic fault are 108 °, 79 ° dipping to SW, and 4 °, respectively. On the whole, the fault is mainly of left-lateral, with a small amount of thrust component and only one co-seismic rupture center in our inversion result. The rupture center is located at a depth of ~5 km below the surface, and the maximum slip is 3.1 m. The total seismic moment released by this earthquake is 1.28 × 1019 N·m, and the corresponding moment magnitude is 6.67. Finally, the static Coulomb stress change results show that parts of the Lenglongling fault, the Tolaishan fault, the Sunan-Qilian fault and the Minyue-Damaging fault are loaded, emphasizing the importance for earthquake risk assessment of these fault.